USE OF BOTULINUM TOXIN IN THE MANAGEMENT OF POST-PAROTIDECTOMY COMPLICATIONS: FREY SYNDROME, SIALOCELE AND SALIVARY FISTULA - Hariasz, Natalia; Arciszewski, Kamil; Orda, Karolina; Walczak, Dominika; Szumiło, Jakub; Kasperska, Klaudia; Markiv, Mariana; Słowik, Michał; Stenzel, Paweł; Świercz, Jędrzej (International Journal of Innovative Technologies in Social Science, 2026)
Background: Parotidectomy is a commonly performed procedure associated with postoperative complications such as Frey syndrome, sialocele, and salivary fistula, which may significantly impair patient quality of life and require additional management. Botulinum toxin is increasingly used as a minimally invasive therapeutic option in this setting. Aim: The aim of this study was to evaluate current evidence regarding the use of botulinum toxin in the prevention and treatment of complications following parotidectomy. Material and methods: This study was designed as a narrative review based on previously published scientific literature. A comprehensive search of PubMed, Scopus, and Google Scholar databases was conducted, including studies published up to 2025. Articles addressing the use of botulinum toxin in Frey syndrome, sialocele, and salivary fistula were included and analyzed qualitatively. Results: The reviewed studies consistently demonstrated high clinical effectiveness of botulinum toxin in the management of post-parotidectomy complications. In Frey syndrome, most patients achieved substantial or complete reduction of gustatory sweating, with therapeutic effects typically lasting 6–12 months. In cases of sialocele and salivary fistula, botulinum toxin reduced salivary secretion, promoted lesion closure, and shortened recovery time compared to conservative management. Reported adverse effects were uncommon and generally mild and transient. Conclusions: Botulinum toxin is an effective and safe option in the management of post-parotidectomy complications. Despite the need for repeated administration in some cases, it represents a minimally invasive alternative to surgical treatment. Further prospective studies are required to establish standardized protocols and long-term outcomes.